Experimental and theoretical studies on structural changes in the microtubule affinity-regulating kinase 4 (MARK4) protein induced by N-hetarenes: a new class of therapeutic candidates for Alzheimer’s disease - Haque, Ashanul; Alenezi, Khalaf M.; Abdul Rasheed, Mohd. Saeed Maulana; Rahman, Md. Ataur; Anwar, Saleha; Ahamad, Shahzaib; Gupta, Dinesh (Frontiers in Medicine, 2025)
IntroductionAlzheimer’s disease (AD) is a neurodegenerative disorder that progressively affects the cognitive function and memory of the affected person. Unfortunately, only a handful of effective prevention or treatment options are available today. Microtubule affinity-regulating kinase 4 (MARK4) is a serine/threonine protein that plays a critical role in regulating microtubule dynamics and facilitating cell division. The dysregulated expression of MARK4 has been associated with a range of diseases, including AD.MethodsIn this study, we synthesized a series of N-hetarenes via Pd(0)-catalyzed Suzuki-Miyaura cross coupling reaction. All compounds were characterized using multi-spectroscopic techniques and evaluated for their activity against the MARK4 enzyme through ATPase inhibition assays. The experimental data was further supported by computational and quantum chemical calculations. We also computed the drug-likeness, bioavailability, and toxicity (ADME/T) profiles of the compounds.ResultsSix new 4-(6-(arylpyrimidin-4-yl)piperazine-1-carboximidamides 5−10 were prepared in good yields. ATPase inhibition assay conducted on these compounds demonstrated IC50 values in micromolar range (5.35 ± 0.22 to 16.53 ± 1.71 μM). Among the tested compounds, 4-(6-(p-tolyl)pyrimidin-4-yl)piperazine-1-carboximidamide (5; IC50 = 5.35 ± 0.22 μM) and 4-(6-(benzo[b]thiophen-2-yl)pyrimidin-4-yl)piperazine-1-carboximidamide (9; IC50 = 6.68 ± 0.80 μM) showed the best activity. The binding constant (K), as determined by the fluorescence quenching assay was estimated to be 1.5 ± 0.51 × 105 M−1 for 5 and 1.14 ± 0.26 × 105 M−1 for 9. The results of molecular docking and MD simulation studies against MARK4 (PDB: 5ES1) indicated that compounds were able to bind the ATP binding pocket of the MARK4, leading to its stabilization. Additionally, ADME/T analysis revealed a high degree of drug-likeness of the compounds.ConclusionWe demonstrated that 4-(6-(arylpyrimidin-4-yl)piperazine-1-carboximidamides) are a promising class of N-hetarenes for developing next-generation anti-AD drugs. The reported class of compounds inhibited MARK4 activity in-vitro at micromolar concentration by targeting the ATP-binding pocket. These findings provide valuable insights for future drug design.